PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE DISCOVERY LEARNING DI MTs PSM RANDUBLATUNG - Hermawan, Muhammad Dhang; Setyawan, Danang Budi (Smart Education, 2024)
The subject of this research is students of MTs PSM Randublatung in the academic year 2023/2024. The initial conditions found in class VII B MTs PSM Randublatung indicate that students' learning outcomes are low or have not met the Minimum Mastery Criteria (KKM), and the learning activities still use lecture methods, resulting in low student learning outcomes. The objectives of this research are to improve (1) student learning outcomes using the Discovery Learning method on the material Characteristics of Living Things for class VII B MTs PSM Randublatung and (2) student motivation using the Discovery Learning method on the Characteristics of Living Things for class VII B MTs PSM Randublatung. This research is conducted through 2 cycles, and the results show that (1) student learning outcomes improved from cycle I to cycle II. In cycle I, those who passed KKM were (41.38%) while those who did not pass were (58.62%). Meanwhile, in cycle II, those who passed KKM were (86.21%) and those who did not pass KKM were (13.79%). The average student learning outcomes also increased. Based on these findings, it can be concluded that the Discovery Learning method can improve student learning outcomes.